An Investigation on Self-Compacting Concrete Using Ultrafine Natural Steatite Powder as Replacement to Cement - P. Kumar; K. Sudalaimani; M. Shanmugasundaram (Advances in Materials Science and Engineering)
An experimental investigation was made on flow properties and compressive strength of self-compacting concrete (SCC) with ultrafine natural steatite powder (UFNSP) as replacement to cement. The tests were conducted on specimens with 5%, 10%, 15%, 20%, and 25% of replacement of UFNSP to the weight of cement and compared to the control specimens. The flow properties of all specimens were tested and checked for their limit with the existing guidelines. The compressive strength test was done on all specimens for strength of 7 days, 14 days, 28 days, and 56 days. The hardened samples were tested for their microstructural behavior and the elements Mg, Ca, and Si were mapped. Through mapping, the formations of M-S-H along with C-S-H are observed. The results show that the addition of UFNSP influences the flow property, by reducing the flow, and increases the compressive strength till 20% replacement. Further the addition of UFNSP increases the denseness of microstructure of the specimens thus resulting in the strength increment.